Everyday barbecue : at home with America's favorite pitmaster - Mixon, Myron (Ballantine Books Trade Paperbacks, 2013)
"Barbecue is a simple food. Don't mess it up. As the winningest man in barbecue, a New York Times bestselling cookbook author, and a judge on the hit show BBQ Pitmasters on Discovery's Destination America, Myron Mixon knows more about smoking meat than any man alive. And now he's on a mission to prove to home cooks everywhere that they can make great barbecue any day of the week--in the comfort of their own backyard or kitchen, no matter their skill level. Across the country at competitions and in his Pride & Joy Bar-b-que restaurants, Mixon has proven that no other pitmaster's food can touch his when he's behind a smoker. But he doesn't need fancy equipment to do it: He can cook delicious barbecue with any grill, smoker, or oven, even on the busiest weeknight, and you'll be able to, too, with the nearly 150 recipes in Everyday Barbecue. Armed with Mixon's advice and tips, you'll discover that barbecue isn't just for the Fourth of July and Labor Day; it's for any day you feel like cooking it. So fire up your grill and get ready to cook incredible barbecue favorites and new classics such as Ribs the Easy Way, Myron's Dr Pepper Can Chicken, and The King Rib sandwich, to more adventurous backyard fare such as Pork Belly Sliders and Barbecue-Fried Baby Backs, with leftover inspirations, delectable deserts, and even some drunken recipes!"--